Evaluation value of subjective visual quality examination on surgical indications of the early cataracts based on objective scatter index values - Yuzhi Li; Ling Jin; Mingfeng Wu; YuKan Huang (Frontiers in Medicine, 2022)
AimTo evaluate the subjective visual functions of early cataracts patients and assess their surgical indications.MethodsEyes were separated into a control group (Group A without cataract) and two early cataracts groups (Group B with 2.0 ≤ OSI < 3.0 and Group C with 3.0 ≤ OSI < 4.0). The objective scatter index (OSI), modulation transfer function cut-off frequency (MTF cut-off), and Strehl ratio (SR) values were applied to measure objective visual functions. The contrast sensitivity (CS) and scores of the questionnaires (QOL and VF-14) characterized subjective visual functions. Above visual functions were compared among three groups. Postoperative visual functions in Group B and C were analyzed to assess the outcome of surgery.ResultsNinety two subjects (126 eyes) were included in the study. All objective visual function in Group B were significantly better than Group C (all P < 0.01), but worse than Group A (all P < 0.01). Except for 1.5 c/d CS, subjective visual function in Group A were significantly better than Group B and C (all P < 0.05), but there was no significant differences between Group B and C. As for eyes that underwent surgery in Group B and C, all visual functions significantly improved after surgery (P < 0.05), except for 1.5 c/d CS in Group C. There were no significant differences among the three groups after surgery.ConclusionThe subjective visual function can be impaired in early cataracts patients with OSI < 3.0, whose objective visual functions were statistically better than patients with OSI ≥ 3.0. These patients can benefit equally from surgery as patients with OSI ≥ 3.0. Subjective visual functions can be used as surgical indications for these patients.